Innervation changes induced by inflammation of the rat thoracolumbar fascia - Hoheisel, Ulrich; Rosner, Jan; Mense, Siegfried (Neuroscience, 2015)
Recently, the fascia innervation has become an important issue, particularly the existence of nociceptive fibers. Fascia can be a source of pain in several disorders such as fasciitis and non-specific low back pain. However, nothing is known about possible changes of the fascia innervation under pathological circumstances. This question is important, because theoretically pain from the fascia cannot only be due to increased nociceptor discharges, but also to a denser innervation of the fascia by nociceptive endings. In this histological study, an inflammation was induced in the thoracolumbar fascia (TLF) of rats and the innervation by various fiber types compared between the inflamed and intact TLF. Although the TLF is generally considered to have proprioceptive functions, no corpuscular proprioceptors (Pacini and Ruffini corpuscles) were found. To obtain quantitative data, the length of fibers and free nerve endings were determined in the three layers of the rat TLF: inner layer (IL, adjacent to the multifidus muscle), middle layer (ML) and outer layer (OL). The main results were that the overall innervation density showed little change; however, there were significant changes in some of the layers. The innervation density was significantly decreased in the OL, but this change was partly compensated for by an increase in the IL. The density of substance P (SP)-positive - presumably nociceptive - fibers was significantly increased. In contrast, the postganglionic sympathetic fibers were significantly decreased. In conclusion, the inflamed TLF showed an increase of presumably nociceptive fibers, which may explain the pain from a pathologically altered fascia. The meaning of the decreased innervation by sympathetic fibers is obscure at present. The lack of proprioceptive corpuscular receptors within the TLF does not preclude its role as a proprioceptive structure, because some of the free nerve endings may function as proprioceptors.
Gesehen am 22.02.2018